A theoretical study on cytosine tautomers in aqueous media by using continuum models - Sambrano, JR; Souza, Aguinaldo Robinson de [UNESP]; Queralt, J. J.; Andres, J. (Elsevier B.V., 2000)
B3LYP/6-31 + + G** and MP2/6-31 + + G** calculations have been carried out to study six tautomers of the nucleic acid base cytosine in aqueous media. Solvent effects have been analyzed using the self-consistent reaction field theory with two continuum methods. Relative stabilities and optimized geometries have been calculated for the tautomers and compared with experimental data. The present results show the importance of electrostatic solvent effects in determining observable properties of the cytosine tautomers. The amino-oxo form (C1) is the most abundant tautomer in aqueous media while the other amino-oxo form (C4) is the most energetically favored when solvent effects are included. These results can be justified by the larger values of the dipole moments for both C1 and C4 tautomers. Theoretical and experimental results of the harmonic vibrational frequencies and rotational constants show good agreement. (C) 2000 Elsevier B.V. B.V. All rights reserved.